2017
DOI: 10.5098/hmt.9.26
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pore Wall Surface Property on Flux of Cylindrical-Shaped Nanoporous Filtering Membrane

Abstract: The influence of pore wall surface property on the flux of a novel cylindrical-shaped nanoporous filtering membrane is analytically studied by using the flow factor approach model for a nanoscale flow. Across the thickness of the membrane are manufactured two concentric cylindrical pores with different radii. The smaller nanoscale pore is for filtration, while the other larger pore is for reducing the flow resistance. It was found that when the larger pore wall surface is hydrophobic, the interaction between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Similar with the membrane shown by Zhang (2017b), the present membrane might be applicable for a liquid-liquid separation. In this section, the results for the applicability of the membrane for liquid-liquid separations are presented.…”
Section: For Liquid-liquid Separationsupporting
confidence: 54%
See 1 more Smart Citation
“…Similar with the membrane shown by Zhang (2017b), the present membrane might be applicable for a liquid-liquid separation. In this section, the results for the applicability of the membrane for liquid-liquid separations are presented.…”
Section: For Liquid-liquid Separationsupporting
confidence: 54%
“…In this section, the results for the applicability of the membrane for liquid-liquid separations are presented. Similar as shown by Zhang (2017b), for a liquid-liquid separation, it is here assumed that the mixed liquids have greatly different interactions with the pore wall in the membrane. The radius ,2 of the trunk pore in the present membrane is determined as optimum according to the liquid with a weak interaction with the pore wall.…”
Section: For Liquid-liquid Separationmentioning
confidence: 99%
“…Satya Narayana and Venkateswarlu (2016) examined heat transfer analysis of water-based nanofluid over a stretching sheet using different types of nanoparticles such as Cu, Ag, TiO2, and Al2O3. One of the problems by Zhang (2017Zhang ( & 2018 of these membranes is their high flow resistances because of nanoscale confining pores, which can result in fairly small fluxes of the membranes. It was shown that this slow flow is due to the nanoscale pore radius, the increased effective viscosity of the liquid in the confining pores and the significant non-continuum effect of the liquid across the pore radius (Zhang, 2016).…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…It was suggested that the depth of the smaller pore should be as small as possible and across the remaining thickness of the membrane should be manufactured the larger pore; By this way, the membrane can achieve an overall good performance characteristics. It was also shown that this membrane can be used for a liquid-liquid separation if the mixed liquids have largely different interactions with the pore walls (Zhang, 2017b).…”
Section: Introductionmentioning
confidence: 99%